An Assessment of Workforce Diversity on Employee Performance in Rural District Councils - T.B, Bhebhe,; Murindi, P, (IJRDO - Journal of Business Management, 2020)
The study investigated the effects of workforce diversity on employee performance by combining qualitative and quantitative research methodologies. Respondents were drawn from rural local authorities in Mashonaland West Province, Zimbabwe. Questionnaires and interviews were used to collect data from a sample size of 169 respondents. The Statistical Package for Social Scientists (SPSS) Version 16.0 and thematic analysis were used to analyse quantitative and qualitative data respectively. The study found that workforce in local authorities was diversified on the basis of age, gender, level of education, political affiliation, experience and in-service duration. Homogeneity among workforce was found on the basis of nationality. It was concluded that that both the primary and secondary dimensions of workforce diversity affected employee performance. Gender diversity had an inverse association with employee performance whilst age diversity was not statistically significant. The study recommended the crafting of inclusive policies and a workforce diversity management framework. Employers were advised to treat different employees differently so as to tap the best out of workforce diversity. It was further recommended that employees should be trained to be tolerant of the differences among themselves.